Virulome and pathogenicity of multidrug-resistant World Health Organization priority pathogens - Esposito, Fernanda Ribeiro dos Santos (2023)
The convergence of hypervirulence and resistance to carbapenems and to polymyxins in pathogens classified by the World Health Organization (WHO) as priority has been increasingly reported for human-animalenvironmental isolates around the world lately, thereby indicating a one health problem. As an integral part of the OneBR project (http://onehealthbr.com/), in the present study, 119 whole genomes of human, animal, environmental, and plant isolates of Escherichia coli (n=1), Klebsiella pneumoniae (n=101), and Pseudomonas aeruginosa (n=17)were sequenced with the aim of identifying the convergence between virulence and resistance. This dissertation is organized into six chapters, as follows: Chapter I Literature review and research justification Up-to-date literature review on pathogenicity, virulome, and convergence in the virulence and resistance of E. coli, K. pneumoniae, and P. aeruginosa isolates that are resistant to carbapenems and/or polymyxins. Chapter II Materials and methods Brief description of the materials and methods used in the research project. Chapter III - Genomic and phenotypic analyses of E. coli isolates Anexo 1 - Mucoviscosity induced by ciprofloxacin in CTX-M-15-producing Escherichia coli carrying the Klebsiella pneumoniae K23 gene cluster. Written article, in the process of finalizing corrections for submission to the International Journal of Antimicrobial Agents (Impact Factor 15.441), presenting for the first time the mucoviscosity phenotype induced by the presence of fluoroquinolones, chiefly ciprofloxacin, in a multiresistant strain of extended-spectrum β-lactamase (ESBL)-producing Escherichia coli isolated from spinach leaves. Interestingly, the genomic analysis of this isolate detected virulence genes in charge of the synthesis of the K23 capsule were identified, confirming the presence of the phenotype observed previously. Moreover, by way of experiments with cells that resembled RAW macrophages, it was possible to identify a larger escape from phagocytosis by cells that had been previously exposed to ciprofloxacin, suggesting that the synthesized capsule is functional. Notably, this is the first report of fluoroquinolone-induced mucoviscosity phenotype in E. coli isolates, and identification of K23 serotype in E. coli isolates. Chapter IV Genomic and phenotypic analyses of K. pneumoniae isolates the K. pneumoniae genome bank, known as KpBR (http://onehealthbr.com/bacteria/KpBr), was developed so as to contribute to the epidemiological surveillance health systems in the management and control of antimicrobial resistance at the human-animal-environmental interface in Brazil. Appendix 2 - Genomic analysis of a Kpi (pilus system)-positive and CTX-M-15-producing Klebsiella pneumoniae belonging to the high-risk clone ST15 isolated from an impacted river in Brazil. Article published (https://doi.org/10.1016/j.ygeno.2021.12.007) in Genomics (Impact factor: 4.31, Qualis CAPES A2), in 2022. Appendix 3 - Successful expansion of healthcare-associated hypervirulent KPC-2- producing Klebsiella pneumoniae ST11/KL64 to impacted aquatic environment. Article published (https:// doi.org/10.1016/j.onehlt.2023.100594) in One Health Journal (Impact factor: 9.00), in 2023. Chapter V Genomic and phenotypic analysis of P. aeruginosa isolates The genome bank of P. aeruginosa, known as PaBr (http://onehealthbr.com/bacteria/PaBr), was developed to contribute to epidemiological surveillance health systems in the management and control of antimicrobial resistance at the human-animal- environmental interface in Brazil. Appendix 4 - Genomic analysis of carbapenem-resistant Pseudomonas aeruginosa isolated from urban rivers confirms spread of clone sequence type 277 carrying broad resistome and virulome beyond the hospital. Article published (https:// doi.org/10.3389/fmicb.2021.701921) in Frontiers in Microbiology (Impact factor: 6.064, Qualis CAPES A1), in 2021. Chapter VI Final remarks Major findings, contributions, and applications obtained from the present study.